Electronic structure and x-ray magnetic circular dichroism in the Mn3CuN perovskite - Antonov, V.N.; Bekenov, L.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2014)
The electronic and magnetic structures of Mn3CuN are investigated theoretically from first principles using the fully relativistic Dirac LMTO band structure method. Mn3CuN possesses a magnetic phase transition at TC = 143 K from a high temperature paramagnetic phase to a low temperature ferromagnetic one with a noncollinear magnetic structure. The transition is accompanied by a structural change from the cubic to the tetragonal lattice. In low temperature phase two Cu moments and two Mn moments (Mn2 and Mn3) ferromagnetically align along the c axis while other four Mn1 magnetic moments are canted from the c axis to [111] direction by angle Q= ±76.2. The x-ray absorption spectra and x-ray magnetic circular dichroism (XMCD) spectra of Mn3CuN are investigated theoretically from first principles. The origin of the XMCD spectra in the Mn3CuN compound is examined. The calculated results are compared with the experimental data.